Pengaruh Kualitas Produk Kopi Terhadap Kepuasan Konsumen: Studi kasus pada kedai kopi “Dari Hati” di Kota Makassar - Rosada, Ida; Nurliani , N; Husain, Tsalis Kurniawan; Khaerudin, Taufik (Journal Galung Tropika, 2023)
A coffee shop (cafe) offers a relaxed atmosphere for fast food and drink. A good cafe can provide satisfaction for consumers in terms of service, affordable products and prices, and adequate equipment and facilities. The research objectives are: (1) Describe the coffee drink production process and (2) Describe product quality. (3) Describe consumer satisfaction with the quality of coffee drink products. (4) Analyzing the influence of coffee drink product quality on consumer satisfaction. The population of this research is consumers who make purchases directly at the "From Heart" coffee shop in Makassar City. The sampling technique was Purposive Sampling, with a total of 100 respondents. The research results show (1) The coffee drink production process begins with procuring and selecting the main ingredients, namely coffee beans, grinding them to become powder, and procuring/selecting additional ingredients in the form of flavor variants. The ground coffee beans are mixed with the flavor variants according to the consumer’s wishes; then, the packaging process is carried out. (2) The quality of the coffee drink product, namely performance, features, aesthetics, and conformance to specifications, is in the "very good" category. (3) The level of consumer satisfaction based on emotional factors, price, and service quality in the "very satisfied" category. (4) The influence of the quality of coffee drink products, namely performance, features, aesthetics, and conformance to specifications, together (F test) or partially (t-test), has a significant effect on consumer satisfaction.